If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + 2) + -1(-3x + 4) = 0 Reorder the terms: (2 + 8x) + -1(-3x + 4) = 0 Remove parenthesis around (2 + 8x) 2 + 8x + -1(-3x + 4) = 0 Reorder the terms: 2 + 8x + -1(4 + -3x) = 0 2 + 8x + (4 * -1 + -3x * -1) = 0 2 + 8x + (-4 + 3x) = 0 Reorder the terms: 2 + -4 + 8x + 3x = 0 Combine like terms: 2 + -4 = -2 -2 + 8x + 3x = 0 Combine like terms: 8x + 3x = 11x -2 + 11x = 0 Solving -2 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 11x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 11x = 0 + 2 11x = 0 + 2 Combine like terms: 0 + 2 = 2 11x = 2 Divide each side by '11'. x = 0.1818181818 Simplifying x = 0.1818181818
| 3x(y+5)=25 | | 2r+3=4r-9 | | 4x+17=12x-79 | | 9x^2+100x-2965550=0 | | 1-6q=-17 | | 3e^2(2x+1)=2e^2-e^2(x+1) | | 3p+2.5=3.7 | | a^2=7a | | (12x^2)+(12y^2)+3x+2y+6=0 | | 8x-y=5 | | v^2-5v=0 | | 13=-4.9t^2+13 | | x^5-5x^4-4x^3= | | 4x+3=3x-8 | | 4x-6=4(x+7) | | 0.4(x+300)=0.46x-348 | | 5(4x-9)-5=5(x-3)+70 | | x^2−7x+4=0 | | −7x+4=3x−5 | | 84=4x÷2 | | x2−7x+4=3x−5 | | x^2−7x+4=3x−5 | | Y=w^2+20w | | 4n+3=5 | | 4n+3=2 | | 36x^2+24=-4 | | 6n+8=10 | | 9=-r-5+11 | | 64x^2+32x=-4 | | 3n+2=6 | | 8y^2+26y+21=0 | | 6x^2*6x^4= |